2022
DOI: 10.17509/ajse.v2i3.39634
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mugwort Leaf Extract and Gotu Kola Leaf Extract against Acne Bacterial Activity

Abstract: Acne is a problem among teenagers generally caused by bacterial infections such as Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Mugwort (Artemisia vulgaris L.) and Gotu Kola (Centella asiatica L.) extracts have antibacterial activity formulated in anti-acne gel preparations. The purpose of this study was to test and obtain a gel formula of mugwort leaf extract and gotu kola leaf extract which effectively kills and controls the growth of acne-causing bacteria. The methods used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In several studies, Flavonoids found in Gotu kola leaves have been shown in multiple trials to reduce acnecausing bacteria (Sari et al, 2022). As a natural disinfectant, a mixture of 1:1 Gotu Kola extract and Aloe Vera can be effective (Mayefis et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, Flavonoids found in Gotu kola leaves have been shown in multiple trials to reduce acnecausing bacteria (Sari et al, 2022). As a natural disinfectant, a mixture of 1:1 Gotu Kola extract and Aloe Vera can be effective (Mayefis et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%